Harnessing Infographic Media to Improve Knowledge of Hypertension Management During Pregnancy - Aprilia, Rizki; Ahmad, Mardiana; Jumrah, Jumrah; Handayani Idrus, Hasta (Journal of Neonatal Surgery, 2025)
Hypertension during pregnancy is a cause of morbidity and mortality in mothers and children worldwide. One of the other factors is that the level of knowledge of hypertensive pregnant women is not optimal due to the lack of information about controlling hypertension. Efforts made to improve the knowledge of pregnant women about hypertension in pregnancy are with various media health education. This research uses the literature review method by searching for sources through the Electronic Data Base. The electronic database used is google scholar which begins with determining topics and keywords for searching articles and journals. Search through PubMed, Google Scholar, and Web of Sciences, Sciences Direct. The research process includes a critical review and assessment of existing literature sources. As well as determining the topic and keywords ‘hypertension, pregnant women, infographic media, and knowledge’ for searching articles and journals in accordance with what the researcher reviewed that infographic media can provide an attractive, effective, and easily accepted form of information for pregnant women. The results show that the use of infographic media is easier to understand, fun because it does not all contain full text and then varied image colours. The findings of this literature show that infographic media can be used as a medium to increase knowledge related to the prevention of hypertension during pregnancy.